The Effectiveness of Flash Card Media in Enhancing English Language Skills of Early Childhood Learners - Putri Ramadani; Zulkifli Surahmat (Synergy Education Journal of Multidisciplinary Language and Social Sciences, 2026)
This study aims to examine the effectiveness of using flash card media in enhancing English language skills of early childhood learners through a literature study approach supported by field observations. Early childhood is a critical period of rapid language development, requiring concrete, engaging, and developmentally appropriate learning media. Flash cards are widely recommended because they provide simultaneous visual and verbal stimulation, enabling children to acquire vocabulary in an enjoyable and meaningful way. This review is based on four relevant journal articles and the researcher’s classroom observations. The literature analysis reveals consistent findings that flash card media effectively improves children’s English language ability, vocabulary mastery, and learning engagement. Ulfa (2020) found that flash cards facilitate learning through play, although their stimulation is primarily visual. Trisnanti et al. (2018) demonstrated a significant effect of bilingual flash cards on English vocabulary acquisition, indicated by a substantial difference in mean scores between experimental and control groups. Furthermore, Sinaga et al. (2023) reported that integrating the Total Physical Response method with flash cards increased learning outcomes by 23.5% compared to conventional methods, due to active learner involvement through movement and visualization. Rustiana and Amiruddin (2025) also reported a notable improvement in language skills, rising from 7% at the initial stage to 80% after two learning cycles. Field observations support these findings, showing that children were more focused, enthusiastic, and responsive when flash cards were used, despite limited variation in practice. Overall, this study concludes that flash cards are an effective and relevant learning medium for developing early childhood English language skills and should be optimized in early childhood education settings.